The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1097/aln.0000000000002726
|View full text |Cite
|
Sign up to set email alerts
|

Midazolam Sedation Induces Upper Limb Coordination Deficits That Are Reversed by Flumazenil in Patients with Eloquent Area Gliomas

Abstract: This article is featured in "This Month in Anesthesiology," page 1A. This article is accompanied by an editorial on p. 5. This article has a related Infographic on p. 17A. This article has an audio podcast.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 23 publications
3
20
0
Order By: Relevance
“…In this issue of Anesthesiology, Lin et al report midazolam-induced upper limb motor deficits in patients with supratentorial gliomas. 2 This aligns with previous work demonstrating that GABAergic agonism unmasks neurologic deficits in patients with brain tumors or cerebrovascular disease. 1,3,4 What is unique in the current study by Lin et al 2 is the demonstration that flumazenil reverses these pharmacologically induced deficits, supporting a GABAergic mechanism.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…In this issue of Anesthesiology, Lin et al report midazolam-induced upper limb motor deficits in patients with supratentorial gliomas. 2 This aligns with previous work demonstrating that GABAergic agonism unmasks neurologic deficits in patients with brain tumors or cerebrovascular disease. 1,3,4 What is unique in the current study by Lin et al 2 is the demonstration that flumazenil reverses these pharmacologically induced deficits, supporting a GABAergic mechanism.…”
supporting
confidence: 90%
“…2 This aligns with previous work demonstrating that GABAergic agonism unmasks neurologic deficits in patients with brain tumors or cerebrovascular disease. 1,3,4 What is unique in the current study by Lin et al 2 is the demonstration that flumazenil reverses these pharmacologically induced deficits, supporting a GABAergic mechanism. Interestingly, motor dysfunction was not restricted to the contralateral limb in this study; ipsilateral motor dysfunction was observed as well, and flumazenil restored baseline function bilaterally.…”
supporting
confidence: 90%
“…One previous study reported that BZD use was a trigger for post-stroke recrudescence ( 15 ). Further, akin to the present work, transient worsening has been noted in patients with space-occupying lesions or an ischemic event specifically with midazolam usage ( 16 19 ). Moreover, there is evidence to support a phenomenon whereby neurological deficits associated with space-occupying lesions or ischemic events from which patients recovered are unmasked by BZD sedation.…”
Section: Discussionsupporting
confidence: 60%
“…Previous studies have reported upon an association between midazolam use and transient unmasking of past neurological deficits ( 17 21 ). Notably, one study demonstrated reversibility of worsened deficits by treatment with flumazenil ( 16 ). This body of literature has been summarized in greater detail within a recent systematic review on this topic ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Lin et al studied 15 adult patients with eloquent area glioma scheduled for elective resection of the tumors. 1 Prior to induction of anesthesia, motor coordination and eye-hand coordination of upper extremity (contralateral or ipsilateral to tumor location) were evaluated using Nine-Hole Peg Test in three phases: baseline (before midazolam), sedation (after midazolam), and reversal (after reversal of midazolam with flumazenil). Endpoint of midazolam administration was to achieve Observer Assessment of Alertness and Sedation score (OAAS) of 4 (i.e., sedated, but arousable and fully cooperative), and the endpoint of flumazenil reversal was to achieve OAAS score of 5 (i.e., fully alert).…”
Section: Reversal Of Midazolam-induced Motor Deficits By Flumazenil In Patients With Eloquent Area Gliomamentioning
confidence: 99%